(untitled) (Conference Zone, 2022)
The article on the intellectual and creative activity of adolescents is especially fruitful when it is devoted to the realization of artistic values. Intelligence and creativity are activated here. In addition, in adolescence there is a keen interest in art and a great need to know it on a logical-cognitive and artistic-aesthetic level. When it comes to highly artistic works (preparing adolescents for their perception and the process itself), logical and artistic thinking develops with maximum activation of creative thinking and imagination, generalization and its own attitude, reproduction. For adolescents, however, this is not enough: the intellectual and creative potential requires its implementation in any cognitive activity. In this process of intellectual and creative development with the result of activities (eg cognitive and educational), the personality of adolescents is formed.